2008
DOI: 10.5194/we-8-74-2008
|View full text |Cite
|
Sign up to set email alerts
|

Life-history traits in an evergreen Mediterranean oak respond differentially to previous experimental environments

Abstract: Living organisms respond both to current and previous environments, which can have important consequences on population dynamics. However, there is little experimental evidence based on long-term field studies of the effects of previous environments on the performance of individuals. We tested the hypothesis that trees that establish under different environmental conditions perform differently under similar post-establishment conditions. We used the slow-growing, evergreen Mediterranean oak Quercus ilex subsp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…Q. ilex is a late successional, slow-growing tree with high capacity of resprouting (Zavala et al 2000). We found that, 21 years after the start of this restoration project, the planted woodland islets have grown in volume and produce large amounts of acorns (Rey Benayas et al 2008b); however, the islets have not increased in area beyond the original planted surface of 100 m 2 . Moreover, whereas a number of holm oaks of different size have established around the islets, there is a ca.…”
Section: Introductionmentioning
confidence: 90%
“…Q. ilex is a late successional, slow-growing tree with high capacity of resprouting (Zavala et al 2000). We found that, 21 years after the start of this restoration project, the planted woodland islets have grown in volume and produce large amounts of acorns (Rey Benayas et al 2008b); however, the islets have not increased in area beyond the original planted surface of 100 m 2 . Moreover, whereas a number of holm oaks of different size have established around the islets, there is a ca.…”
Section: Introductionmentioning
confidence: 90%
“…However, we used an experimental approach rather than a phenomenological approach to test the effects of environmental manipulation on soil properties. Our study is part of long-term research aiming to investigate the effects of environmental manipulation on ecosystem processes in relation to restoration of Mediterranean woodland (Cayuela et al, 2008;Rey Benayas et al, 2008a). In this context, we also evaluated the relevance of previous management in addition to current environmental conditions on soil chemistry of the reforested woodland.…”
Section: Introductionmentioning
confidence: 99%
“…Se han realizado numerosos estudios sobre la eficacia en las plantaciones de uno o varios cuidados culturales simultáneos y/o posteriores al establecimiento (Reque y Bravo 1993;Peñuelas et al, 1996;Lemieux y Delisle, 1998;Rey et al, 2002;Rey y Camacho, 2004;Rey et al, 2005;Rey et al, 2008;Badano et al, 2009;Palmerlee y Young, 2010;Kribeche et al, 2012;Pardos et al, 2015). Estos estudios muestran que los cuidados culturales reducen la mortalidad de las plantas sustancialmente y ofrecen buenos ratios beneficio/inversión (Rey y Camacho 2004;Dey et al, 2008).…”
Section: Los Cuidados Culturalesunclassified